Use of glucometer and fasting blood glucose as screening tools for diabetes mellitus type 2 and glycated haemoglobin as clinical reference in rural community primary care settings of a middle income country - Muktabhant Benja; Sanchaisuriya Pattara; Sarakarn Pongdech; Tawityanon Worawitaya; Trakulwong Mantana; Worawat Songsri; Schelp Frank P (BMC, 2012)
Abstract Background Thailand is considered to be a middle income country, and to control and prevent type 2 diabetes mellitus (T2DM) is one of the main concerns of the Thai Ministry of Public Health (MoPH). Screening for T2DM and care for T2DM patients has been integrated into the primary health care system, especially in rural areas. The intention of this investigation is to link public health research at the academic level with the local health authorities of a district of a north-eastern province of the country. Methods Epidemiological methods were applied to validate the screening tools fasting capillary blood glucose (CBG), measured by glucometer and venous blood for the determination of plasma glucose (VPG), used for screening for T2DM among asymptomatic villagers. For assessing the validity of these two methods glycated haemoglobin (HbA1c) values were determined and used as the 'clinical reference'. Results All together 669 villagers were investigated. Determinations of CBG and VPG resulted in suspected T2DM cases, with 7.3% when assessed by CBG and 6.4% by VPG using a cutoff point of 7 mmol/L (126 mg/dl). Taking HbA1c determinations with a cutoff point of 7% into account, the proportion of T2DM suspected participants increased to 10.4%. By estimating sensitivity, specificity and the positive predictive value of CBG and VPG against the 'clinical reference' of HbA1c, sensitivity below 50% for both screening methods has been observed. The positive predictive value was determined to be 58.5% for CBG and 56.8% for VPG. The specificity of the two screening tests was over 96%. Conclusions The low sensitivity indicates that using fasting CBG or VPG as a screening tool in the field results in a high proportion of diseased individuals remaining undetected. The equally low positive predictive values (below 60%) indicate a high working load for the curative sector in investigating suspected T2DM cases to determine whether they are truly diseased or false positive cases according to the screening method. Further implications of the results and the controversial discussion related to the use of HbA1c as clinical evidence for suffering from T2DM are also discussed.